2023
DOI: 10.1021/acsapm.3c01893
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Wearable Sensor Based on Tough, Self-Healing, Adhesive Polyurethane Elastomer for Human Motion Monitoring

Yang Bai,
Zhong Jing,
Boyuan Zhang
et al.

Abstract: Although some progress has been achieved in flexible strain sensors, it is still a big challenge to develop sensors with excellent self-healing capability, adhesive, and recyclable properties for enhanced lifespan, facile operation, and decreased waste pollution in the flexible electronic field. In this study, we successfully synthesized the pyrene-terminated multifunctional polyurethane elastomer called PMFPU based on dynamic covalent bond and noncovalent hydrogen bonds, which integrates exceptional tough mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It was observed that as the temperature increased, all mechanical performance indicators improved, consistent with the earlier test results. To highlight the innovation in our work, Figure f compares the LNPU-3 with reported self-healing polyurethanes in terms of tensile strength, self-healing temperature, and self-healing period. , LNPU-3 demonstrates a leading position in all three aspects, providing more options for 3D printing materials and exploring additional possibilities for the application of self-healing materials.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that as the temperature increased, all mechanical performance indicators improved, consistent with the earlier test results. To highlight the innovation in our work, Figure f compares the LNPU-3 with reported self-healing polyurethanes in terms of tensile strength, self-healing temperature, and self-healing period. , LNPU-3 demonstrates a leading position in all three aspects, providing more options for 3D printing materials and exploring additional possibilities for the application of self-healing materials.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of self-healing materials, the introduction of self-healing materials into wearable devices can not only improve the intelligence of wearable devices but also improve the reliability of their operation and extend their service life. Self-healing PU materials based on dynamic bonds can be used in a wide range of electronic devices, such as tactile sensors, 147 bending sensors, 148,149 strain sensors, 150–153 humidity sensors, 154 proximity sensors, 155 actuators, 156 electromyography sensors, 157 electrocardiogram sensors, 158 and light-emitting electrochemical cell displays. 159 The self-healing matrix is often combined with inorganic or metallic conductive materials to realize the integration of self-healing properties and sensing functions.…”
Section: Potential Applicationsmentioning
confidence: 99%